2015
DOI: 10.1093/mnras/stv1023
|View full text |Cite
|
Sign up to set email alerts
|

High-energy cosmic neutrinos from spine-sheath BL Lac jets

Abstract: We recently proposed that structured (spine-sheath) jets associated to BL Lac objects offer a suitable environment for the production of the extragalactic high-energy (E > 100 TeV) neutrino recently revealed by IceCube. Our previous analysis was limited to low-power BL Lac objects. We extend our preliminary study to the entire BL Lac population. We assume that the power of cosmic rays as well as the radiative luminosity of the sheath depend linearly on the the jet power. In turn, we assume that the latter is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 82 publications
4
92
0
1
Order By: Relevance
“…90% C.L. upper limits on the (n n + m m ) flux for models of the neutrino emission from (a) generic blazars (Mannheim 1995;Halzen & Zas 1997;Protheroe 1997), (b) BL Lacs (Mücke et al 2003;Padovani et al 2015;Tavecchio & Ghisellini 2015), and (c)+(d) FSRQs (Becker et al 2005;Murase et al 2014). The upper limits include a correction factor that takes into account the flux from unresolved sources (see Appendix C) and systematic uncertainties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…90% C.L. upper limits on the (n n + m m ) flux for models of the neutrino emission from (a) generic blazars (Mannheim 1995;Halzen & Zas 1997;Protheroe 1997), (b) BL Lacs (Mücke et al 2003;Padovani et al 2015;Tavecchio & Ghisellini 2015), and (c)+(d) FSRQs (Becker et al 2005;Murase et al 2014). The upper limits include a correction factor that takes into account the flux from unresolved sources (see Appendix C) and systematic uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…These include the calculations by Mannheim (1995), Halzen & Zas (1997), and Protheroe (1997) for generic blazars; the calculations by Becker et al (2005) and Murase et al (2014) for FSRQs; and the calculations by Mücke et al (2003), Tavecchio et al (2014), Tavecchio & Ghisellini (2015), and Padovani et al (2015) for BL Lacs.…”
Section: Upper Limits On Models For Diffuse Neutrino Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various extragalactic scenarios have been suggested that might be (partially) responsible for the observed flux of neutrinos. Source candidates include galaxies with intense star formation [28,29,30,31,32,33], cores of active galactic nuclei (AGN) [34,35,36], low-luminosity AGN [37,38], blazars [39,40,41], low-power GRBs [42,43,44], cannonball GRBs [45], intergalactic shocks [46], and active galaxies embedded in structured regions [47,48,29].…”
Section: Pos(icrc2015)022mentioning
confidence: 99%
“…[3,4] and has since then been explored in a number of studies (see e.g. [5][6][7][8][9]). We perform here detailed statistical studies to test a blazar connection with UHECRs going through high energy neutrinos used as "intermediaries".…”
Section: Introductionmentioning
confidence: 99%